Analysis of Teacher Quality and Teaching Methods on the Use of Information and Communication Technology (ICT) and its Implications for Learning Quality (Case Study at Smkn 5 Bandung) - Eka Rachman (CV. Publikasi Indonesia, 2026)
This research aims to analyze the influence of teacher quality and learning methods on ICT utilization and its impact on learning quality at SMKN 5 Bandung, both partially and simultaneously, with ICT as an intervening variable. The study uses a quantitative survey method with 83 teacher respondents. Data were analyzed through descriptive and verifiable analysis using SPSS path analysis. The descriptive results showed that teacher quality, learning methods, and learning quality were in the medium category, while ICT utilization was in the high category. Verifiable analysis showed that teacher quality and learning methods simultaneously had a significant effect on ICT utilization (R² = 0.488). Partially, learning methods had a significant effect on ICT utilization (ρ = 0.775; Sig. < 0.001), while teacher quality did not show a significant effect. ICT utilization has a positive and significant effect on learning quality (path coefficient = 0.342; R² = 79.3%). Learning methods also had a direct effect on learning quality (ρ = 0.500), while teacher quality did not show a significant influence. Path analysis showed that the indirect effect of learning methods through ICT (26.5%) was greater than the direct effect (25.0%). Simultaneously, teacher quality and learning methods have a significant effect on learning quality. The study concludes that learning methods and ICT utilization are dominant factors in enhancing learning quality at SMKN 5 Bandung, while teacher quality still requires optimization, particularly in ICT integration.